RANCANGAN PAKET WISATA KECAMATAN MEMPURA KABUPATEN SIAK - Feranita Fitri Heryani; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Mempura Subdistrict has a variety of tourism potentials ranging from natural wealth, artificial tourism, historical relics, Malay art and culture as well as a silent witness to the government of the Siak Kingdom after being transferred from Artificial. This writing aims to compile a Tour Package based on the tourism potential in Mempura District. This research uses a qualitative method with a descriptive approach, the subjects of the study are the Siak Regency Tourism Office, Mempura District Office, and tourist attraction managers . Data collection is carried out through literature studies, observations, interviews and documentation. The results of this study show that in Mempura District there are natural attractions, Cultural Attractions and Artificial attractions . Accessibility to Mempura District is very easy to reach through land access and also water and road conditions are quite good. The amenity in Mempura District is quite complete and there is an Anciliary that houses tourist attractions in Mempura District. The packages offered are mass tourism 1 day tour packages with river crossing tour packages and royal tours priced at Rp.60,000/pax, sholawat orange harvest packages priced at Rp.51,000/pax and durian collapse packages priced at Rp.55,000/pax as well as special interest tourism packages 2 Days 1 Night cruising Mempura tours at a price of Rp.439,000/pax Keywords : Tour Packages, Design, Mempura Subdistrict